Análisis histórico de los programas de educación física portugueses (1948-2000) = Historical analysis of portuguese physical education programs (1948-2000) - Antonio Pereira (Universidad Politécnica de Madrid, 2011)
Se trata de una revisión histórica de la evolución de los Programas oficiales que en Portugal han estado vigentes desde 1948 hasta el 2000, a través del análisis de los elementos de su desarrollo curricular y del tipo de curriculum empleado; lo que lleva al autor, a la conclusión de que han existido grandes diferencias didácticas entre los actuales Programas y los empleados anteriormente, que redujeron la materia de Educación Física a una mera "animación deportiva".   Abstract: This is an historical review of the official programs that have been in force in Portugal from 1948 to 2000, carried out by means of an analysis both of the elements of its curricular development and of the type of curriculum used; such analysis makes the author conclude that there have been great differences from an educational point of view between today's programs and those previously used, which reduced the subject of Physical Education to simply "taking part in sport".